The Substance and Relevance of the Concept of Maintenance in the Family: A Thematic- Holistic Combination Study - Nur Hayati Aulia; Moh. Fawwaz Khitam Romadloni (PALAR | PAKUAN LAW REVIEW, 2026)
This study discusses the concept of family livelihood with a thematic-holistic approach to explore its substance and relevance in the context of contemporary life. Livelihood is an important obligation in the family institution regulated in the Qur'an, Hadith, and reinforced by the views of scholars and legal systems in various Muslim countries. Thematic studies explore verses and hadiths related to livelihood to formulate a complete understanding, while the holistic approach emphasizes the importance of considering universal Islamic values ​​in the practice of providing livelihood. The results of the study show that the concept of livelihood is not only material, but also a moral responsibility that aims for the sustainability of household life and its fulfillment is interpreted flexibly based on the agreement of husband and wife and is very relevant in answering the dynamics of modern families. Amidst changes in social structures and gender roles, the principles of justice, responsibility, and equality remain at the core of Islamic teachings on livelihood. This study emphasizes the importance of reinterpreting basic Islamic values ​​to maintain family harmony in the modern era. Keywords: Livelihood, concept, thematic-holistic, relevance.